ANALISIS PERFORMANCE POMPA FEED SENTRIFUGAL - Erwinsyah, Mochamad Dava Erwinsyah; Bismantolo, Putra; Witanto, Yovan (UNIB Press, 2023)
To support the optimization of operations at a refinery, a tool is urgently needed that can help process crude oil into a product. The centrifugal feed pump P-100/4 is a pump that operates in a distillation unit where the distillation unit functions to process oil from crude oil into products such as residue, diesel ph, diesel, kerosene, naptha and petrasol. The centrifugal feed pump P-100/4 aims to pump crude oil from tanks 101 and 102 to provide feed to furnace 5, before entering the crude oil furnace which is preheated in heat exchangers 1,2,3 to 4. The P-100/4 feed centrifugal pump is driven by a motor. In this paper more focused on the operation and maintenance of centrifugal pump P-100/4 feed. This data collection method is carried out by conducting interviews with field supervisors, and observing the pump unit directly, and other supporting books. The results obtained are: With a good and correct pump operator system and with capable and skilled operators, the pump operation will always be in good condition, and the life of the pump will be longer. The NPSHa value of the P. 100/4 mash pump meets the operating specifications, which is greater than the NPSHr. So the P.100/4 pump does not experience cavitation so the pump work is very stable. The efficiency price of the P. 100/4 feed pump is 68.40%